Development of N,N’-diacetylchitobiose as coating containing antimicrobial agent for ready-to-eat food product - Zainal Abidin, Munira (2019)
N,N’-diacetylchitobiose (GlcNAc2) is known to be highly functional, soluble in water and offers a wide range of applications, especially as an antimicrobial agent. In this study, we aim to explore the use of thermal pre-treatment on chitin, prior hydrolysis to produce GlcNAc2. The compound has been assessed for its antimicrobial activity against food pathogenic strains, as well as its effectiveness as an antimicrobial coating on ready-to-eat (RTE) cooked shrimp. A thermal pre-treatment process using an autoclave, has been employed to facilitate subsequent enzymatic hydrolysis of chitin with chitinase from Streptomyces griseus. Pre-treatment of chitin with 0.05 M sodium acetate buffer (pH=6.0) at 121 ºC for 60 min, followed by enzymatic hydrolysis involving 24 h incubation, were found to be the best conditions for producing GlcNAc2. The GlcNAc2 obtained was tested for its antimicrobial activity against Gram-negative and Gram-positive strains and showed minimum inhibitory concentrations (MIC) at 5 and 10% w/v against Escherichia coli K-12 and Listeria monocytogenes 10403S, respectively. The inhibitory effect of 1% (w/v) GlcNAc2 used as antimicrobial coating on RTE cooked shrimp was studied at 4 ᵒC for 16 days. In addition, the quality of the shrimp meat was also determined. The results indicated that the GlcNAc2 coating retarded the changes in texture properties, TBARS values and moisture content of the RTE shrimp during storage. The incorporation of GlcNAc2 coating did not significantly change the shrimp colour in comparison with the control. However, the growth of L. monocytogenes inoculated on the GlcNAc2-coated RTE shrimp was slower than control sample, and the highest log reduction observed was 0.5 log CFU/mL. This study shows that autoclaving of chitin facilitates subsequent enzymatic hydrolysis to form a mixture dominating in GlcNAc2, which possesses antimicrobial activity that is able to inhibit food pathogenic strains and maintain the quality of ready-to-eat shrimp during refrigerated storage.